Fluvastatin inhibits Rab5-mediated IKs internalization caused by chronic Ca2+-dependent PKC activation. (April 2019) - Parks, Xiaorong Xu; Ronzier, Elsa; O-Uchi, Jin; Lopes, Coeli M.
Abstract: Statins, in addition to their cholesterol lowering effects, can prevent isoprenylation of Rab GTPase proteins, a key protein family for the regulation of protein trafficking. Rab-GTPases have been shown to be involved in the control of membrane expression level of ion channels, including one of the major cardiac repolarizing channels, IKs. Decreased IKs function has been observed in a number of disease states and associated with increased propensity for arrhythmias, but the mechanism underlying IKs decrease remains elusive. Ca 2+ -dependent PKC isoforms (cPKC) are chronically activated in variety of human diseases and have been suggested to acutely regulate IKs function. We hypothesize that chronic cPKC stimulation leads to Rab-mediated decrease in IKs membrane expression, and that can be prevented by statins. In this study we show that chronic cPKC stimulation caused a dramatic Rab5 GTPase-dependent decrease in plasma membrane localization of the IKs pore forming subunit KCNQ1, reducing IKs function. Our data indicates fluvastatin inhibition of Rab5 restores channel localization and function after cPKC-mediated channel internalization. Our results indicate a novel statin anti-arrhythmic effect that would be expected to inhibit pathological electrical remodeling in a number of disease states associated with high cPKC activation. Because Rab-GTPases are important regulators of membrane trafficking they may underlie other statin pleiotropic effects.